Pengaruh Integrasi Pemasok pada Kinerja Rantai Pasok dengan Mediasi Kinerja Pemasok - Nasar Buntu Laulita (Journal of Global Business and Management Review, 2019)
This study aims to investigate the influence of supplier integration to supply chain performance by moderating effect of supplier performance. The methodology of this research is an explanatory study by testing three hypotheses. The data’s were collected from a convenience samples of 171 manufacturing companies of total 850 companies in Batam being represented by manager in supply chain management divisions. Data’s were collected using questionnaire and technical data analysis using SEM (Structural Equation Model). The result of this study found that: (1) Organization Culture affects Supplier Integration positively and significantly; (1) Supplier Integration affects Suplier Performance positively but not signifivantly; (2) Supplier Performance affects Supply Chain Performance positively but not signifianctly; (3) Supplier Integration affects Supply Chain Performance positively and significantly. The managerial implication of this research is as a guidance for decision maker in the company or manager in the supply chain management to implement Supplier Integration and consider the location of supplier when selected key supplier to improve Supply Chain Performance.